Gambaran Pengetahuan Masyarakat tentang Dagusibu Obat Antibiotik di Rw 001 Kelurahan Tamalanrea Jaya Kota Makassar Tahun 2023 - AR., Nurul Izza; Rysma, Putri (Jurnal Farmasi Sandi Karsa, 2023)
Antibiotics are therapy to treat bacterial infections. Antibiotics must be used rationally to optimize their function. According to a study from the National Academy of Sciences (NAS) of the United States, antibiotic use increased 65.0% from 2000 to 2015. One way to properly and correctly manage antibiotic drugs is through DAGUSIBU socialization. A preliminary survey was conducted on 5 residents, 1 person had good knowledge and 4 people had poor knowledge regarding the use and disposal of antibiotics. The aim of this research is to determine the level of public knowledge about the antibiotic drug DAGUSIBU in RW 001, Tamalanrea Jaya Village, Makassar City in 2021. This research uses a quantitative descriptive survey method. The sampling technique used is non-probability sampling. Data collection was carried out based on primary data in the form of a questionnaire, with a total of 50 respondents. The results of the study showed that knowledge about how to obtain antibiotic drugs was 58.0% in the quite good category, knowledge about how to use antibiotic drugs was 66.0% in the quite good category, knowledge about how to store antibiotic drugs was 84.6% in the good category. and knowledge about how to dispose of antibiotic drugs was 76.0% in the quite good category.